Sea cucumbers of the genus Labidodemas (Holothuroidea: Holothuriida: Holothuriidae) from Indonesia, with the description of a new species and a revised key to the genus - Setyastuti, Ana; Solis-Marin, Francisco Alonso; Lüter, Carsten (Zootaxa, 2024)
The present paper describes two often-reported species of Labidodemas as present in Indonesia: L. rugosum (Ludwig, 1875) and L. semperianum Selenka, 1867, and describes a new species to science Labidodemas javaensis sp. nov. from the shallow water of Java Island. The new species is distinguished from its congeners by having (1) most table discs devoid of peripheral holes with rim of the discs very spiny, (2) dorsal papillae and ventral tube feet that always have two types of tables (regular table with crown spines always bifurcate distally and smaller table size with very spiny disc and crown), and (3) the presence of a tri-radiate shape of rods in the dorsal body wall and anal papillae. Nine species are now recognised as valid within the genus Labidodemas, and five of them are found on the Indonesian sea floor. Furthermore, we also observed Cuvierian tubules in some individuals of L. rugosum and L. semperianum. The latter observation supports the argumentation to best-keep Labidodemas at the generic level within Holothuriidae.